2022
DOI: 10.26508/lsa.202101263
|View full text |Cite
|
Sign up to set email alerts
|

Human BRCA pathogenic variants were originated during recent human history

Abstract: BRCA1 and BRCA2 (BRCA) play essential roles in maintaining genome stability. BRCA germline pathogenic variants increase cancer risk. However, the evolutionary origin of human BRCA pathogenic variants remains largely elusive. We tested the 2,972 human BRCA1 and 3,652 human BRCA2 pathogenic variants from ClinVar database in 100 vertebrates across eight clades, but failed to find evidence to show cross-species evolution conservation as the origin; we searched the variants in 2,792 ancient human genome data, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…This is evidenced by the fact that nearly all currently known BRCA founder mutations determined by haplotyping were young, for example, BRCA1 c.3228_3229del in Italian was arisen 3,225 yr ago (Laitman et al, 2013); of the three BRCA founder mutations in Ashkenazi Jewish population, BRCA1 185delAG(c.68_69del) was arose 1,500-750 yr ago (Hamel et al, 2011), BRCA1 5382insC(c.5266dup) 1,800 yr ago (Neuhausen et al, 1998), and BRCA2 6174delT(c.5946del) 580 yr ago (Zeegers et al, 2004); BRCA2 c.9118-2A>G, a founder mutation in Icelander population, was arisen only 220-144 yr ago (Altmann & Gennery, 2016). Our recent study also revealed that human BRCA deleterious variants mostly arose after migration out-of-Africa and great expansion of modern human population (Li et al, 2022). This may also be related with differences of evolution selection on different DDR genes.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This is evidenced by the fact that nearly all currently known BRCA founder mutations determined by haplotyping were young, for example, BRCA1 c.3228_3229del in Italian was arisen 3,225 yr ago (Laitman et al, 2013); of the three BRCA founder mutations in Ashkenazi Jewish population, BRCA1 185delAG(c.68_69del) was arose 1,500-750 yr ago (Hamel et al, 2011), BRCA1 5382insC(c.5266dup) 1,800 yr ago (Neuhausen et al, 1998), and BRCA2 6174delT(c.5946del) 580 yr ago (Zeegers et al, 2004); BRCA2 c.9118-2A>G, a founder mutation in Icelander population, was arisen only 220-144 yr ago (Altmann & Gennery, 2016). Our recent study also revealed that human BRCA deleterious variants mostly arose after migration out-of-Africa and great expansion of modern human population (Li et al, 2022). This may also be related with differences of evolution selection on different DDR genes.…”
Section: Discussionmentioning
confidence: 59%
“…Two third of DDR deleterious variants were present only in single ethnic populations. It suggests that DDR deleterious variants could be most likely arisen in recent history (Keinan & Clark, 2012;Fu et al, 2013;Li et al, 2022). This is evidenced by the fact that nearly all currently known BRCA founder mutations determined by haplotyping were young, for example, BRCA1 c.3228_3229del in Italian was arisen 3,225 yr ago (Laitman et al, 2013); of the three BRCA founder mutations in Ashkenazi Jewish population, BRCA1 185delAG(c.68_69del) was arose 1,500-750 yr ago (Hamel et al, 2011), BRCA1 5382insC(c.5266dup) 1,800 yr ago (Neuhausen et al, 1998), and BRCA2 6174delT(c.5946del) 580 yr ago (Zeegers et al, 2004); BRCA2 c.9118-2A>G, a founder mutation in Icelander population, was arisen only 220-144 yr ago (Altmann & Gennery, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, they are not be suitable to classify the missense variants in BRCA1 and BRCA2 , as the pathogenic variants in BRCA1 and BRCA2 were mostly originated in recent human history rather than evolution conservation from other species. 52 On the contrary, DL-RP-MDS uses protein structure as the reference to identify abnormalities caused by missense variants by following the thermodynamics changes to differentiate benign and deleterious variants. Furthermore, DL-RP-MDS can tolerate the altered residues and allocate deleterious probability with high BA values.…”
Section: Discussionmentioning
confidence: 99%
“…The process followed the detailed procedures described in our previous publication [ 13 ]. Briefly, the reference sequences used in annotating human MUTYH variants were: hg38 NC_000001.11 for the genomic position, NM_012222 for cDNA and NP_036354 for protein.…”
Section: Methodsmentioning
confidence: 99%